Effectiveness of early clinical exposure in medical education: Settings and scientific theories - Review - Motilal Chandu Tayade; Ramchandra Girimalappa Latti (Wolters Kluwer Medknow Publications, 2021)
Early clinical exposure (ECE) is a teaching-learning methodology which fosters the exposure of medical students to the patients as early as the first year of medical college. A worldwide number of research studies investigated the outcome of ECE and found, ECE sessions motivate the medical student in various ways making their academic strength, improve clinical skills, and improve communication skills and making them more confident. In the medical curriculum, ECE makes an overall impact on student's performance and confidence. Planning of ECE in real-time practices can be done in different settings with the use of appropriate resources such as logbook, textbooks, notes, instruments, learning material, case record sheets, and computers. Herewith, we reviewed the scientific base responsible for these outcomes and discussed different ECE settings and their outcome. The Medical Council of India in new educational reforms made ECE sessions compulsory from 2019 in undergraduate medical curriculum. In conclusion, the challenge for health professions education is to look for ways to improve the quality of clinical education by comparing students' understanding and modifying practices of clinical education in new circumstances. Early clinical experience will definitely play a crucial role in this context, only if proper strategies are implemented. This systemic review article highlights ECE settings and scientific basis in a theoretical way helpful for medical faculties during its implementation in regular teaching.